Ceftazidime and Usnic Acid Encapsulated in Chitosan-Coated Liposomes for Oral Administration against Colorectal Cancer-Inducing Escherichia coli - Jaqueline Barbosa de Souza; Davi de Lacerda Coriolano; Rayza Camila dos Santos Silva; Sérgio Dias da Costa Júnior; Luís André de Almeida Campos; Iago Dillion Lima Cavalcanti; Mariane Cajubá de Britto Lira Nogueira; Valéria Rêgo Alves Pereira; Maria Carolina Accioly Brelaz-; Isabella Macário Ferro Cavalcanti (MDPI AG, 2024)
Escherichia coli has been associated with the induction of colorectal cancer (CRC). Thus, combined therapy incorporating usnic acid (UA) and antibiotics such as ceftazidime (CAZ), co-encapsulated in liposomes, could be an alternative. Coating the liposomes with chitosan (Chi) could facilitate the oral administration of this nanocarrier. Liposomes were prepared using the lipid film hydration method, followed by sonication and chitosan coating via the drip technique. Characterization included particle size, polydispersity index, zeta potential, pH, encapsulation efficiency, and physicochemical analyses. The minimum inhibitory concentration and minimum bactericidal concentration were determined against E. coli ATCC 25922, NCTC 13846, and H10407 using the microdilution method. Antibiofilm assays were conducted using the crystal violet method. The liposomes exhibited sizes ranging from 116.5 ± 5.3 to 240.3 ± 3.5 nm and zeta potentials between +16.4 ± 0.6 and +28 ± 0.8 mV. The encapsulation efficiencies were 51.5 ± 0.2% for CAZ and 99.94 ± 0.1% for UA. Lipo-CAZ-Chi and Lipo-UA-Chi exhibited antibacterial activity, inhibited biofilm formation, and preformed biofilms of E. coli. The Lipo-CAZ-UA-Chi and Lipo-CAZ-Chi + Lipo-UA-Chi formulations showed enhanced activities, potentially due to co-encapsulation or combination effects. These findings suggest potential for in vivo oral administration in future antibacterial and antibiofilm therapies against CRC-inducing bacteria.